2014
DOI: 10.1080/21580103.2014.940001
|View full text |Cite
|
Sign up to set email alerts
|

Climate–growth relationships of relictPicea jezoensisat Mt. Gyebang, South Korea

Abstract: A study was conducted to evaluate climatic variation at Mt. Gyebang, South Korea, and its influence on the modelled and observed growth of its relict Picea jezoensis population. Using the MT-CLIM and Biome-BGC models, year-to-year meteorological variation and subsequent changes in growing season, primary productivity and water balance were simulated. These were compared with the observed growth of sample P. jezoensis trees at the site. According to weather data and model calculations, the P. jezoensis stand at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Furthermore, P. jezoensis is vulnerable to global warming with declining competitiveness in South Korea. (7,8) In this study, we only considered the climatic factors as environmental parameters. Further study is needed to perform more comprehensive modeling research with various environmental parameters of P. jezoensis, such as growth conditions, soil, and altitude.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, P. jezoensis is vulnerable to global warming with declining competitiveness in South Korea. (7,8) In this study, we only considered the climatic factors as environmental parameters. Further study is needed to perform more comprehensive modeling research with various environmental parameters of P. jezoensis, such as growth conditions, soil, and altitude.…”
Section: Discussionmentioning
confidence: 99%
“…(5,6) Furthermore, P. jezoensis is vulnerable to global warming with declining competitiveness in South Korea. (7,8) P. jezoensis has been designated as an endangered species in Korea and categorized as of Least Concern (LC) in the International Union for Conservation for Nature (IUCN)'s Red List of Threatened Species. (9) Hence, this species is of great conservation importance in South Korea, owing to its restricted distribution and ecological value.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another local scale study conducted on a spruce community in a mountains area, Mt. Gyebangsan, also showed that climate change between 1972 and 2006 advanced the start date of spruce growth and delayed the end date, resulting in an increase in the growing season of spruce; however, this increase in growing season was not statistically significantly correlated with spruce growth (Jang et al 2015).…”
Section: Ecosystem: Biota In the Current State Phenologymentioning
confidence: 97%